THE EFFECT OF TALENT MANAGEMENT, LEADERSHIP STYLE AND HEALTHCARE EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL PERFORMANCE IN OMAN GOVERNMENT HOSPITALS - Khalood Farzah; Nor Azilah Husin (International Journal of Accounting, Finance and Business, 2024)
Oman's medical environment. Furthermore, the significance of this study—which focuses on healthcare professionals' involvement as a mediator between talent management and hospital performance—is underscored by the need for additional research on talent management and retention in healthcare settings. By examining the connection between leadership, talent management, and hospital performance in Omani public hospitals, the study seeks to close a gap in the literature. The goal of the research is to gain a thorough understanding of the variables influencing the participation of healthcare workers and how those aspects affect the operation of Omani government hospitals. The report highlights the value of talent management and HEE for guaranteeing sustainability and improving hospital performance. The study's measurement scale proved to be valid and dependable, which made it useful for assessing Omani hospitals' talent management procedures. A useful foundation for comprehending the connection between talent management, HEE, and hospital performance is offered by the study's structural model. Furthermore, this study highlights how important the resource-based view theory is for understanding the connection between talent management and healthcare. professionals hospital performance and engagement using a single model. The study demonstrates how talent management affects hospital performance and contributes to the expanding body of research on talent management in hospitals, particularly in Oman. The study highlights the importance of talent management frameworks in determining healthcare professionals engagement in hospitals, which is critical for enhancing hospital performance. This research has several practical outcomes for hospital managers, highlighting the potential challenges and pitfalls associated with HEE and talent management. The study's findings can have significant economic implications for Oman's healthcare sector by improving the efficiency and effectiveness of hospital operations and promoting better patient outcomes. This research's theoretical, methodological, and managerial contributions provide valuable insights that can inform future studies on talent management and healthcare performance.